(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2019)
Buying and selling transactions in Islam is growing along with the development of the age and technology. This is certainly a challenge for Muslims to be able to further examine the transactions that are developing, one of which is buying and selling training videos on the pre-employment card website. Does the practice of buying and selling from related parties is in accordance with the Shari’a or vice versa. Therefore this study intended to find out the procedures for buying and selling contained on the pre-employment card website, as well as the Islamic legal view of the transaction. This study uses a qualitative approach with concept analysis, in which the researcher collected reading sources that are related to the subject matter being studied. The results of this study, First, there were indications of gharar in the video transaction process. Secondly, Ma’qud ?alaih did not know the level of the training video, how many minutes or hours, the video can be used or not, what video content the buyer did not know for sure, and the seller also did not tell about it before. So there were indications that buyers felt be cheated or disappointed with the video because it did not match with buyer expectations.